Asymptotic behavior of dispersive electromagnetic waves in bounded domains - Nicaise, Serge; Pignotti, Cristina (Zeitschrift für angewandte Mathematik und Physik, 2020)
We analyze the stability of Maxwell equations in bounded domains taking into account electric and magnetization effects. Well-posedness of the model is obtained by means of semigroup theory. A passitivity assumption guarantees the boundedness of the associated semigroup. Further the exponential or polynomial decay of the energy is proved under suitable sufficient conditions. Finally, several illustrative examples are presented.